2018
DOI: 10.1371/journal.pone.0200015
|View full text |Cite
|
Sign up to set email alerts
|

Entinostat reverses P-glycoprotein activation in snail-overexpressing adenocarcinoma HCC827 cells

Abstract: Epithelial-to-mesenchymal transition (EMT) in cancer cells facilitates tumor progression by promoting invasion and metastasis. Snail is a transcriptional factor that induces EMT, while P-glycoprotein (P-gp) is an efflux transporter involved in anticancer drug resistance, and P-gp efflux activity is stimulated in Snail-overexpressing lung cancer cells with EMT characteristics. Since the histone deacetylase (HDAC) inhibitor entinostat (Ent) reverses EMT features, our aim in this study was to determine whether En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…[23,24] Moreover, the functional evaluation method of the efflux transporter suitable for each cell has already been established. [22][23][24] Based on those reports, this method to evaluate P-gp and BCRP activity has been selected in each cell. When Ezr or Msn expression was silenced in HCC827 cells, down-regulation of BCRP transport activity occurred; however, knockdown of Rdx did not affect the efflux rate of SN-38 ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[23,24] Moreover, the functional evaluation method of the efflux transporter suitable for each cell has already been established. [22][23][24] Based on those reports, this method to evaluate P-gp and BCRP activity has been selected in each cell. When Ezr or Msn expression was silenced in HCC827 cells, down-regulation of BCRP transport activity occurred; however, knockdown of Rdx did not affect the efflux rate of SN-38 ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, it seems that the regulation of P‐gp function by ERM proteins is tissue‐dependent . Additionally, our earlier report concluded that P‐gp function was enhanced without any increase in its mRNA or whole protein levels when epithelial–mesenchymal transition (EMT) was induced in non‐small‐cell lung cancer cells . Other researchers have reported that ERM protein expression was increased when EMT was induced in cancerous cells .…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations